Asia-Pacific trade and investment report 2011 post-crisis trade and investment opportunities. - United Nations. Economic and Social Commission for Asia and the Pacific (New York United Nations Economic and Social Commission for Asia and the Pacific, 2011)
The Asia-Pacific region has made a vigorous comeback from the global economic crisis and is currently leading world economic growth. However, not all countries have benefited equally from this rebound. Furthermore, as the second decade of the twenty-first century proceeds, the region faces various challenges, such as high food and fuel prices, continued malaise in most of the developed economies, and a higher incidence of natural disasters that affect trade and investment. At the same time, there are also plenty of opportunities. With its focus on the theme Post-crisis trade and investment opportunities, this year's Asia-Pacific Trade and Investment Report identifies the challenges and opportunities for trade and investment in the region. The report concludes that, with the right policies and strengthened regional cooperation, the region would be able to continue its strong trade- and investment-led growth.
Keywords: Asia -- Economic policy; Asia -- Commerce; Pacific Area -- Economic policy; Pacific Area -- Commerce